Possibilities for development of social education and social educational services for a family at children’s day care centres - Daiva Alifanovienė; Odeta Šapelytė; Nomeda Bėčiūtė (Social Welfare: Interdisciplinary Approach)
The article deals with the specificity of social education and socioeducational services for children from socially disadvantaged families provided at children’s day care centres and possibilities of development of these services in the aspect of family members’ social inclusion. The article presents the analysis of qualitative semi-structured interviews. Content analysis targeted at experiences of children’s day care centre professionals (N = 10) highlights the content of learners’ social education at children’s day care centres and of provided socioeducational services for the family, expressed through professionals’ subjective assessment of  the current situation and the need for services to be provided.